Implementation and Impact of Lean Manufacturing: A Critical Review and Framework for Adoption - Darshan H Bhalodia; Rishabh D Makwana; Parth M Lakum; Rohit R Raval; Heena M. Patel (International Journal of Industrial and Product Design Engineering, 2025)
Lean manufacturing has become a vital approach for organizations seeking to enhance efficiency, reduce waste, and strengthen competitiveness in dynamic industrial environments. Although lean principles are well established, industries continue to experience inconsistencies in implementation outcomes due to differences in organizational readiness, employee involvement, and managerial commitment. This study critically reviews existing research on lean manufacturing to examine its practical impact, the factors influencing its success, and the challenges that hinder sustainable adoption. Through an analysis of global case studies and scholarly contributions, the paper evaluates the effectiveness of core lean tools—such as 5S, Kaizen, Value Stream Mapping, Just-in-Time production, and Total Productive Maintenance—in improving process flow, reducing variability, and fostering continuous improvement The review highlights that while lean practices consistently improve productivity, quality, and cost performance, their benefits often remain limited when implementation is fragmented or lacks cultural integration. Common barriers include inadequate training, resistance to change, insufficient monitoring systems, and limited leadership engagement. To address these constraints, the study proposes a structured Lean Adoption Framework comprising seven stages: organizational diagnosis, strategic alignment, process mapping and waste identification, pilot testing, capability development, full-scale integration, and ongoing evaluation supported by feedback loops. This framework provides a practical roadmap to guide industries in adopting lean systematically and sustainably The findings emphasize that lean manufacturing yields long-term operational advantages when treated as a continuous improvement philosophy rather than a short-term cost-cutting initiative. The proposed framework serves as a reference for researchers and practitioners aiming to strengthen lean implementation strategies and achieve sustained operational excellence.
Keywords: SMEs; continuous improvement; lean implementation; lean manufacturing; sustainable manufacturing; waste reduction